2018
DOI: 10.5603/rj.2018.0002
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Types of Operable Early Breast Cancer in the Elderly: Is there a Special Pattern? – a Retrospective, Multicentre Study

Abstract: Introduction: The aim of this study was to determine the pattern of histopathological types of breast cancer in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Well-differentiated (G1) carcinomas were diagnosed more often in patients 80+ compared to the control group, while poorly differentiated (G3) carcinomas were diagnosed in the < 80 group, but the difference was not significant. This observation is consistent with data reported in the literature [6,[21][22][23]. However, some investigators have shown significant differences in tumor differentiation, suggesting a more favorable biology of breast cancer in the elderly [24,25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Well-differentiated (G1) carcinomas were diagnosed more often in patients 80+ compared to the control group, while poorly differentiated (G3) carcinomas were diagnosed in the < 80 group, but the difference was not significant. This observation is consistent with data reported in the literature [6,[21][22][23]. However, some investigators have shown significant differences in tumor differentiation, suggesting a more favorable biology of breast cancer in the elderly [24,25].…”
Section: Discussionsupporting
confidence: 92%
“…Similar relationships (3 times higher percentage of deaths than incidence) were observed in the male population, with 23 occurrences at age ≥ 80 (15.4% of total incidence) and 36 deaths (43.3% of breast cancer deaths). It is believed that breast cancers in older women have a milder course, grow more slowly, and are more often of a favorable histopathological type than in younger people [6]. This may suggest potential for a less aggressive treatment in this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancers detected with screening mammography are less likely to metastasize to lymph nodes and more likely to be treated with breast conservation treatment without chemotherapy compared to those women who declined screening [ 14 , 26 ]. In our study, individuals that underwent screening mammograms were more likely to have stage 0 or early staged breast cancers and estrogen and luminal A hormone expression which are considered favorable characteristics [ 26 ]. Interestingly, epidemiology studies have reported that triple-negative breast cancers are more common in women of African ancestry in comparison to others ethnic groups [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%